Optimal Design of PID-Load Frequency System Based on a Sine Cosine Algorithm - Ali Jasim Mohammed (Misan Journal of Engineering Sciences)
The demand on the electricity is changed daily based on the needs of consumers. In this instance, the power generation and power demand will not munch, resulting in, fluctuating frequency in power grid. To solve this problem, a load frequency control (LFC) is created. A proportional integral dravite control (PID) is wildly utilized to design the LFC due to a simpler design. However, it is an unable to address the high oscillation case in frequency response because of its fixed parameters. In this research, the optimal PID-FLC control is designed using the sine cosine algorithm (SCA). A two-area power system network is proposed based on a MATLAB environment in order to evaluate this suggested method. Then, an integral time absolute error (ITAE) index is applied to calculate the transiting time of frequency response when the unpredictable load is change dramatically. The outcomes prove that the LFC system based on PID-SCA technique reduces the overshoot and minimize the steady state error at simple and complex disturbances. As results, it achieves an acceptable ITAE index about 6.8 seconds when it is compared with the conventional PID-FLC which reaches to 17.4 second under the complex load-change.